Cores e sabores das frutas - Elias, Eliane Gonzalez; Feijó, Giane Felix; Fernandes, Marta Cordeiro; Bordinhão, Andréia; Carraro, Márcia Regina Simpioni (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
VER PDF